Blendas de polipropileno e polietileno linear de baixa densidade com nanocargas de montmorilonita compatibilizadas com copolímero etileno-octeno - Borba, Caroline Henrique de Souza (2022)
Linear low-density polyethylene and polypropylene are among the most consumed polymers worldwide. The unique properties of these polymers allow their application to be extended to the production of blends or the insertion of nanofillers in their matrix. However, both the production of blends, as well as the insertion of nanofillers in their matrix, require the use of additives such as compatibilizing agents and coupling agents that help in the process of compatibilization and interaction between matrix/nanofiller. This work sought to evaluate the different types of coupling agents, in the mechanical, morphological and thermal properties of PP/LLDPE blends compatible with EOC and with montmorillonite nanofillers (MMT). It was verified that the presence of coupling agents acted in the process of exfoliation and/or intercalation of clay lamellae in the blend. The blends with MMT showed values of modulus and yield stress superior to the others. On the other hand, the compositions containing EOC showed higher values of resistance to impact. For compositions with 10phr of EOC the morphology changed from cocontinuous to droplets. The presence of the dispersed phase delayed the onset of matrix crystallization and is related to the degree of interaction of both polymers in the molten state.